ON LINE CONSUMER REVIEWS, SECURITY AND RISK PERCEPTION ON ON LINE PURCHASE DECISION AT LAZADA - Fachrurazi Fachrurazi (JURNAL DARMA AGUNG, 2023)
In order to overcome difficulties in shopping online, Lazada needs to review the influence of online consumers reviews, security and perception risk to decision purchase consumer .Study this aim for analyze influence on line consumer reviews, security, and perception risk on online purchasing decisions. The problems raised in this study are not enough its popular site on line Lazada, total visitors which still a little compared to site others, and various issues related to online consumer review, security, and perception risk. Respondents in this study were Pelita Indonesia Pekanbaru students with a total of a sample of 95 people. Methods of data analysis using multiple linear regression analysis method with test t and f for testing hypothesis. Results study prove that variable on line consumer reviews, security and perception risk have influence which positive and significant to decision purchase in a manner on line in Lazada.